Corrigendum “Veget ation impact on the dune stabi lity and formation on the Lithuanian coast of the Baltic sea” - Urbonienė, Ramunė; Kelpšaitė, Loreta; Borisenko, Ingrida (Journal of Environmental Engineering and Landscape Management, 2015)
"Corrigendum. ’Veget ation impact on the dune stabi lity and formation on the Lithuanian coast of the Baltic sea’."Journal of Environmental Engineering and Landscape Management, 23(4), p. 312 First published online: 23 Nov 2015